Enhancing interprofessionalism in shared decision-making training within homecare settings: a short report. Issue 1 (2nd January 2020) - Dogba, Maman Joyce; Menear, Matthew; Brière, Nathalie; Freitas, Adriana; Emond, Julie; Stacey, Dawn; Légaré, France
ABSTRACT: Training in shared decision-making (SDM) often focuses solely on dyadic relationships between one healthcare provider and one patient. However, many healthcare decisions often involve two or more health professionals. These decisions warrant utilizing an interprofessional shared decision-making (IP-SDM) approach which enables patients and their caregivers to face difficult decisions around care together. Most existing SDM training programs fall short when building interprofessional (IP) competencies and require an approach that integrates IP with SDM. This short report discusses the creation and trial implementation of three enhanced education tools (a video, role-play exercise with decision aid, and an IP observation aid) for an IP-SDM workshop focused on helping homecare teams collaborate with seniors and their caregivers throughout the decision-making process. We developed and implemented these tools in eight study sites of a larger randomized control trial to test the training workshop for homecare teams. The workshop and tools helped participants overcome interprofessional challenges in their work. Participants evaluated the tools and workshop, which offered guidance to better translate teachable IP collaboration competencies within SDM.